Evaluation of High Schools in the Basque Autonomous Community - José Francisco Lukas Mujika; Karlos Santiago Etxeberria (Universidad Autónoma de Baja California, 2004)
The objective of this paper is to present the high school evaluation model being applied in the Basque Autonomous Community (Spain). This has the purpose of offering relevant information for establishing processes of change and institutional improvement in each of the participating schools. It analyzes, on the one hand, the theoretical bases that underlie it, and on the other, the more relevant methodological and technical aspects of this experience. Together with the description, there is presented a detailed description of the dimensions analyzed, as well as of the collection and construction of the tests and questionnaires used, the current situation and the perspectives for the future.